2008
DOI: 10.1002/chem.200800007
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Chemistry of the cyclo‐(P5tBu4) Ion: Monomeric and Oligomeric Copper(I), Silver(I) and Gold(I) Complexes

Abstract: [Na{cyclo-(P(5)tBu(4))}] (1) reacts with [CuCl(PCyp(3))(2)] (Cyp=cyclo-C(5)H(9)) and [CuCl(PPh(3))(3)] (1:1) to give the corresponding copper(I) complexes with a tetra-tert-butylcyclopentaphosphanide ligand, [Cu{cyclo- (P(5)tBu(4))}(PCyp(3))(2)] (2) and [Cu{cyclo-(P(5)tBu(4))}(PPh(3))(2)] (3). The CuCl adduct of 2, [Cu(2)(mu-Cl){cyclo-(P(5)tBu(4))}(PCyp(3))(2)] (4), was obtained from the reaction of 1 with [CuCl(PCyp(3))(2)] (1:2). Compounds 2 and 3 rearrange, even at -27 degrees C, to give [Cu(4){cyclo- (P(4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 72 publications
2
41
0
3
Order By: Relevance
“…In view of the results obtained in the reactions of [Na(thf) 4 ][cyclo-(P 5 Bu t 4 )] (39) with complexes of the nickel triad, the coordination chemistry of the cyclo-(P 5 Bu t 4 ) − ion towards group 11 complexes was explored. Here, it was also observed that the reactivity of the cyclic anion is notably dependent on the metal, its co-ligands and the reaction conditions [58].…”
Section: Reactivity Of the Cyclo-(p 5 Bu T 4 ) − Ion Towards Transitimentioning
confidence: 92%
See 4 more Smart Citations
“…In view of the results obtained in the reactions of [Na(thf) 4 ][cyclo-(P 5 Bu t 4 )] (39) with complexes of the nickel triad, the coordination chemistry of the cyclo-(P 5 Bu t 4 ) − ion towards group 11 complexes was explored. Here, it was also observed that the reactivity of the cyclic anion is notably dependent on the metal, its co-ligands and the reaction conditions [58].…”
Section: Reactivity Of the Cyclo-(p 5 Bu T 4 ) − Ion Towards Transitimentioning
confidence: 92%
“…Low-temperature 31 the metal, resulting in trigonal-planar copper complexes 75 and 76 and linear gold complex 80 (Fig. 24) [58]. In 77, the P 5 ring bridges a Cu 2 Cl fragment via the anionic and an adjacent phosphorus atom.…”
Section: Reactivity Of the Cyclo-(p 5 Bu T 4 ) − Ion Towards Transitimentioning
confidence: 99%
See 3 more Smart Citations